Mineral composition of hydrothermal chimneys sampled with ROV during Pourquoi Pas ? cruise INDEX2016 - Yuchen Han; Giorgio Gonnella; Nicole Adam; Axel Schippers; Lia Burkhardt; Stefan Kurtz; Ulrich Schwarz-Schampera; Henrike Franke; Mirjam Perner (PANGAEA, 2021)
Hydrothermal chimneys were collected by a ROV in 2016 from the Kairei and Pelagia vent fields along the Indian Ridge. Major element compositions of the chimney samples were determined by a combination of ICP emission and mass spectrometry. For semi-quantitative analysis of sulfide mineral distribution polished sections of the chimneys were investigated by optical and scanning electron microscopy and electron microprobe analyses. The abundance of bacterial and archaeal taxa was determined by sequencing of the 16S rRNA gene by Illumina MiSeq.